Using Wearable Devices to Stimulate Students Motor of Physical Activity and Consequence Physcological Responce - Stradze, Aleksandr E. (2020)
They presented the results of qualitative and quantitative indicator study concerning the motor activity of schoolchildren of both sexes, obtained by using individual wearable devices-fitness trackers. It was found that 8.2% of students, regardless of gender and age, are characterized by low values of this indicator; 3.4% demonstrate high values of the indicator relative to the hygiene norm.